2023
DOI: 10.1155/2023/7064236
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analyzing the Relationship among Social Capital, Dynamic Capability, and Farmers′ Cooperative Performance Using Lightweight Deep Learning Model: A Case Study of Liaoning Province

Abstract: The purpose of this study is to understand the relationship between social capital and the performance of Farmers' Cooperatives (Cooperatives) and explore the internal mechanism of social capital affecting the performance of Cooperatives. This work selects two dimensions: cognitive social capital (CSC) and structural social capital (SSC), as indexes to measure the social capital of Cooperatives. An analytical framework is proposed: “Social capital-Dynamic capabilities-Organizational performance.” First, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Some scholars use principal component analysis, factor analysis, and analytic hierarchy processes to build an evaluation system for the development level of FPCs. In the latest research, scholars have discussed the impact of factors such as information technology and social capital on the performance of FPCs (Wardhiani et al, 2023;Zhang & Wu, 2023). However, some studies on the impact of cooperative development on agricultural TE discuss the impact and role of FPCs on specific industry TE from a micro perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars use principal component analysis, factor analysis, and analytic hierarchy processes to build an evaluation system for the development level of FPCs. In the latest research, scholars have discussed the impact of factors such as information technology and social capital on the performance of FPCs (Wardhiani et al, 2023;Zhang & Wu, 2023). However, some studies on the impact of cooperative development on agricultural TE discuss the impact and role of FPCs on specific industry TE from a micro perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%